Structure, synthesis, and properties of single-metal-atom chains - Ma, Mingyu (2023)
Structural engineering of nanomaterials down to the atomic scale, for example, isolated single atoms, single-atom chains, and single-atom layers, is of interest due to their unique properties and numerous promising applications. In particular, single-metal-atom chains that confine electrons in one-dimensional structures show many one-dimensional quantized behaviors, for example, Tomonaga-Luttinger liquid behavior, high-temperature superconductivity, and fluctuation. These properties could lead to innovative applications in electronics, magnetism, spintronics, catalysis, and beyond. This perspective provides an overview of the research progress made on single-metal-atom chains. We first highlight the recent developments in synthetic strategies for single-metal-atom chains, later summarize the observations of the unusual physicochemical properties, and finally point out current challenges and potential directions.